Real-world effectiveness and safety of tenofovir amibufenamide in treatment-naïve chronic hepatitis B: a 48-week retrospective cohort study - Jiarui Zheng; Yuxuan Song; Bo Feng; Yandi Xie (Frontiers in Medicine, 2026)
Objectives Tenofovir amibufenamide (TMF) is a newly recommended first-line nucleos(t)ide analogues for chronic hepatitis B (CHB) in China. However, real-world evidence on its safety and effectiveness are limited. This study aimed to evaluate the short-term virological efficacy, biochemical response, as well as safety profile of TMF over 48 weeks in a real-world cohort of CHB individuals. Methods In this single-center retrospective cohort study, 129 treatment-naïve CHB patients were administered TMF at 25 mg daily. Clinical, virological, and biochemical parameters were gathered at baseline and at weeks 12, 24, and 48 for evaluation. The primary effectiveness endpoint was virological response (VR, HBV DNA <10 IU/mL) after 48 weeks of treatment. Secondary endpoints included VR at other timepoints, alanine aminotransferase (ALT) normalization, and changes in renal parameters and lipid levels. Results At week 48, 72.9% (94/129) of patients achieved VR. Multivariate analysis identified lower baseline HBsAg levels, HBeAg negative status and non-cirrhotic status as independent predictors for achieving VR. The ALT normalization rate was 77.5% (100/129) at week 48. One patient achieved HBsAg seroclearance. Regarding safety, no adverse events linked to the medication were observed. There were no statistically significant alterations in serum phosphorus, estimated glomerular filtration rate, serum creatinine, or lipid levels (triglycerides, total cholesterol, high-density lipoprotein and low-density lipoprotein) from baseline to week 48. Conclusion In this single-arm observational cohort, TMF treatment achieved effective virological suppression and high rates of ALT normalization by week 48, with renal function and lipid levels remaining stable. Because the study lacked a comparator group, these findings should be regarded as observational. Comparative conclusions about the safety or superiority of TMF relative to tenofovir disoproxil fumarate (TDF) or tenofovir alafenamide (TAF) require dedicated head-to-head studies.